2012
DOI: 10.1200/jco.2012.42.0505
|View full text |Cite
|
Sign up to set email alerts
|

OCEANS: A Randomized, Double-Blind, Placebo-Controlled Phase III Trial of Chemotherapy With or Without Bevacizumab in Patients With Platinum-Sensitive Recurrent Epithelial Ovarian, Primary Peritoneal, or Fallopian Tube Cancer

Abstract: GC plus BV followed by BV until progression resulted in a statistically significant improvement in PFS compared with GC plus PL in platinum-sensitive ROC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
846
4
22

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,208 publications
(901 citation statements)
references
References 22 publications
29
846
4
22
Order By: Relevance
“…There is evidence that the addition of bevacizumab to the regimen of carboplatin and gemcitabine improves progression-free survival compared with carboplatin and gemcitabine in platinum-sensitive disease [80].…”
Section: Chemotherapy For Recurrent Epithelial Malignanciesmentioning
confidence: 99%
“…There is evidence that the addition of bevacizumab to the regimen of carboplatin and gemcitabine improves progression-free survival compared with carboplatin and gemcitabine in platinum-sensitive disease [80].…”
Section: Chemotherapy For Recurrent Epithelial Malignanciesmentioning
confidence: 99%
“…(Table 1), bevacizumab (Avastin) was the first anti-angiogenesis agent to be advanced into the phase 3 randomized trial design for advanced EOC. To date, four pivotal trials have been completed, two in the primary setting and two for patients with recurrent disease (Table 2) [57][58][59][60][61][62][63][64][65][66].…”
Section: Phase 2 Studiesmentioning
confidence: 99%
“…OCEANS, an industry sponsored trial, evaluated the efficacy and safety of bevacizumab in the treatment of patients with recurrent, platinum sensitive ovarian cancer [61]. This trial was initiated in response to GOG 170D, which indicated response to single agent bevacizumab in platinum sensitive and platinum refractory disease [44].…”
Section: Phase 2 Studiesmentioning
confidence: 99%
“…OCEANS [10] was a randomized phase III trial testing the combination of gemcitabine and carboplatin with or without the addition of bev given concurrently and then as maintenance until progression in platinum-sensitive OC. PFS for the bev arm was 12.4 months (vs. 8.4 months; p , .001).…”
Section: Recurrent Diseasementioning
confidence: 99%